A Comparative Legal Analysis of Competition Law Protections for MSMEs in ASEAN Member States - R. Benny Riyanto; Sucihatiningsih Dian Wisika Prajanti; Dina Silvia Puteri (International Law Discourse in Southeast Asia, 2026)
This research analyzes the adequacy of legal protection for Micro, Small, and Medium Enterprises (MSMEs) against trade monopoly practices within the rapidly evolving digital market landscape of the Industrial Revolution 4.0 era. Although Indonesia’s Law Number 5 of 1999 provides preventive safeguards—such as prohibitions on anti-competitive agreements under Articles 5–8—and repressive mechanisms through administrative and criminal sanctions under Articles 30–37, these provisions remain structurally limited in addressing digital-platform dominance and algorithm-driven market distortions. The normative gap between traditional competition law and contemporary digital market realities necessitates a reassessment of MSME protection. Employing a normative legal research design with a statute approach, conceptual approach, comparative approach, and law-and-policy analysis, this study evaluates whether Indonesia’s current framework sufficiently responds to digital-era challenges. Comparative examination of Malaysia, Singapore, and Thailand demonstrates more adaptive regulatory models that integrate digital market oversight into competition law—evident in Malaysia’s Competition Act 2010 and MyDIGITAL Blueprint, Singapore’s enforcement by the Competition and Consumer Commission (CCCS) over dominant online platforms, and Thailand’s Trade Competition Act 2017, aligned with Thailand 4.0. These jurisdictions illustrate a functional convergence toward platform regulation, data transparency, and digital market fairness. This research argues that Indonesia must harmonize its competition policy with digital transformation by adopting platform-specific rules, strengthening algorithmic accountability, and integrating MSME-focused digital market protections. By situating business competition law within the broader digital-economy governance discourse, the study contributes a socio-legal and policy-oriented framework for promoting equitable and sustainable market participation for MSMEs in ASEAN’s digitalized economy.